Swine viscera preservation in hypersaturated salt solution after alcohol fixation as a preparation method for educational purposes. (29th September 2021) - Guaraná, Julia Belotto; Müller, Alois Foltran; Strefezzi, Ricardo de Francisco; Oliveira, Fabrício Singaretti; Machado, Luciana Cristina; Ambrósio, Carlos Eduardo; Dória, Renata Gebara Sampaio; Freitas, Silvio Henrique de
Abstract: The use of live animals for educational purposes is an old practice that is still employed in teaching and research institutions. However, there are several objections to this practice, whether for ethical or humanitarian reasons. Surgical techniques teaching using anatomical pieces and/or preserved cadavers promotes greater learning efficiency, provides exercise repetition and increases the confidence and satisfaction of the students when compared to the use of live animals. The current work aimed to analyse the feasibility of using fresh swine urinary bladder and small intestines (jejunum), obtained from slaughterhouses, fixed in 99.8% ethyl alcohol (EA) and preserved in sodium chloride hypersaturated solution (SCHS) at 30%, for 7, 14 and 21 days, as an alternative method for surgical skills training (SST). Swine viscera, fixed in EA and preserved in SCHS, presented a realistic appearance, absence of odour and maintained the viable morphological characteristics during the performance of the operative techniques. Preservation solutions had low cost, were easy to acquire and did not offers risks to human health. Therefore, urinary bladders and small intestines fixed in 99.8% EA for 30 days and maintained in 30% SCHS at different periods were demonstrated as a good viable option as a preservation method for surgical skills training.